Strictly sincere best responses under approval voting and arbitrary preferences - Carlos Alós-Ferrer; Johannes Buckenmaier (University of Zurich, Department of Economics, 2018)
Approval voting allows voters to support as many candidates as they wish. One advantage of the method is that voters have weak or no incentives to vote insincerely. However, the exact meaning of this statement depends on how the voters' preferences over candidates are extended to sets. We show that, under a combination of standard, well-established assumptions on the extended preferences, voters will always have a strictly sincere best response (that is, a best response ballot such that every approved candidate is strictly preferred to every disapproved one) given the ballots of other voters. The result holds for arbitrary preferences over candidates, allowing for indifferences but covering the extreme cases of dichotomous or strict preferences. As a corollary, we show that the classical strategy-proofness result for the case of dichotomous preferences on alternatives (Brams and Fishburn, 1978) holds for a larger class of preferences on sets than originally assumed.
Keywords: C72; D71; D72; 330; Approval voting; manipulation; preferences among sets; strict sincerity